DESIGN OF REINFORCED CONCRETE STRUCTURE WITH ORDINARY MOMENT FRAME IN LOW SEISMIC REGION (CASE STUDY: MIDRISE SHOPPING BUILDING IN SINGKAWANG CITY) - Zulshaec, Yongga; Herwani, Herwani; Yusuf, Muhammad (Fakultas Teknik Universitas Tanjungpura, 2024)
This paper focuses on the design of a reinforced concrete structure for an eight-story shopping building in Singkawang City, located in a low to moderate seismic area. The study integrates relevant design considerations in response to the region's seismic conditions. Through structural analysis, the building is categorized as seismic design category B due to moderate seismic risk, leading to the selection of an ordinary moment-resisting frame system compliant with SNI 1726:2019. Emphasis is placed on the importance of using such a system to enhance ductility and prevent brittleness during earthquakes.The research emphasizes the need to design structures capable of withstanding various loads, including dead, superimposed dead, live, wind, and earthquake loads, particularly in West Kalimantan, known for its historically low to moderate seismic activity. Recent earthquake records highlight the necessity of earthquake-resistant design for safety and durability. Structural analysis confirms the building's stability against seismic forces, with a modal participation ratio meeting SNI 1726:2019 requirements, indicating robust response under seismic loads.The study also assesses inter-story drift and P-Delta effects to ensure they meet allowable limits, which is crucial for preserving structural integrity and preventing post-earthquake instability. A detailed reinforcement design following SNI 2847:2019 enhances structural strength and durability, especially when under seismic loading. The foundation design uses tailored hollow spun piles to provide sufficient bearing capacity and stability. This approach demonstrates resilience against potential seismic events in low-to-moderate seismic regions, highlighting the importance of integrating seismic design principles and ductility considerations for effective earthquake hazard mitigation.